A 10 MeV RF linac for industrial applications. (5th July 2016) - Nayak, B.; Bhattacharjee, D.; Acharya, S.; Tillu, A.R.; Shivchandan, Shivchandan; Chavan, R.B.; Choudhury, N.; Tiwari, R.
Abstract: This paper discusses the studies on a standing wave, biperiodic, on-axis coupled cavity RF linac operated at 2856 MHZ used for various industrial applications. Results of beam transmission experiments conducted in this accelerator have been presented. Analytical study and experimental verification of steady state beam loading in this facility have been explained. Finally some of the irradiation experiments performed in this system have been described.